Characterization and modeling of TIPS-pentacene-poly(3-hexyl) thiophene blend organic thin film transistor - Mansouri, S.; El Mir, L.; Al-Ghamdi, Ahmed A.; Al-Hartomy, Omar A.; Al Said, Said A. Farha; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2013)
Thin film transistor based on the blend of 6,13-bis(triisopropylsilylethynyl)-pentacene (TIPS-pentacene) and the poly(3-hexylthiophene) (P3HT) was made on SiO2 insulator layers by spin coating method. The blend of TIPS-pentacene and P3HT was prepared for molar ratio of TIPS: P3HT = 1:0.4 ml. Electrical characteristics of the blend of TIPS-pentacene and P3HT transistors under dark and white light illuminations were analyzed. We have exploited the experimental curves current-voltage of our TFT to extract electrical parameters such us mobility, threshold voltage, sub-threshold voltage and trapped density under dark and white light illumination. Finally we have studied the effect of white light illumination on threshold voltage of the organic thin film transistor based on the blend of TIPS-pentacene and P3HT. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: (TIPS-pentacene P3HT)-TFT; Electrical parameters; Effect of white light illumination